2018
DOI: 10.1371/journal.pone.0193346
|View full text |Cite
|
Sign up to set email alerts
|

An informational view of accession rarity and allele specificity in germplasm banks for management and conservation

Abstract: Germplasm banks are growing in their importance, number of accessions and amount of characterization data, with a large emphasis on molecular genetic markers. In this work, we offer an integrated view of accessions and marker data in an information theory framework. The basis of this development is the mutual information between accessions and allele frequencies for molecular marker loci, which can be decomposed in allele specificities, as well as in rarity and divergence of accessions. In this way, formulas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Results of the present study showed a similar number of alleles (56) and average number of alleles (3.29) to results of Choi et al [28] (number of alleles = 51; average number of alleles = 3.0), while genetic diversity (0.490) in the present study was higher than (0.398) in the previous study. Reunova et al [12] have reported similar results (average number of alleles: 2.49; expected heterozygosity (He): 0.453) in 139 individual ginseng plants using 11 SSR primers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results of the present study showed a similar number of alleles (56) and average number of alleles (3.29) to results of Choi et al [28] (number of alleles = 51; average number of alleles = 3.0), while genetic diversity (0.490) in the present study was higher than (0.398) in the previous study. Reunova et al [12] have reported similar results (average number of alleles: 2.49; expected heterozygosity (He): 0.453) in 139 individual ginseng plants using 11 SSR primers.…”
Section: Discussionsupporting
confidence: 86%
“…Such uniqueness makes them prone to be absent in whole collections and their subsets, albeit their potential importance as a source of important traits for plant breeding. Novel strategies in germplasm management are needed to preserve those alleles, prone to be lost, which can be potentially useful for plant breeding, especially in a scenario of rapid climate change that represents serious threats to worldwide food production [56].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that this type of allele, likely to be maintained by deleterious mutation-selection balance, would be of less interest; they seldom contribute to the improvement of elite varieties and, therefore, their inclusion in the CC might not be worthwhile [7,56,57]. In contrast, other authors have more recently proposed core subsets focused on preserving rare accessions and uncommon alleles, which may have unique genetic potentials for plant breeding [58]. In our case, the high number of accessions possessing specific rare alleles makes it difficult to retain a greater number of very rare alleles without increasing the sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Germplasm banks play an important role in the conservation, management and utilization of germplasm resources that is critical for the development of plant breeding [42]. Molecular genetic markers are widely used in germplasm identification and they are important in the construction and management of germplasm banks [43]. For example, the single nucleotide polymorphism (SNP) markers were used to identify Dimocarpus longan L. germplasm [44] and Discorea alata L. germplasm [45].…”
Section: Management and Utilization Of Germplasm Resourcesmentioning
confidence: 99%
“…For example, the single nucleotide polymorphism (SNP) markers were used to identify Dimocarpus longan L. germplasm [44] and Discorea alata L. germplasm [45]. Reyes-Valdés et al offered an integrated view of accession rarity and allele specificity in germplasm banks for management and conservation [43]. Storme et al [46] analyzed 675 P. nigra L. accessions from nine European gene banks using SSR markers, amplified fragment length polymorphism (AFLP) markers and isozyme systems to estimate the extent of duplication and the genetic diversity within and between banks.…”
Section: Management and Utilization Of Germplasm Resourcesmentioning
confidence: 99%